THE NEED TO IMPROVE THE MORALITY OF SENIOR PERSONNEL IN THE MANAGEMENT OF THE STATE AND SOCIETY (Scientific journal of the Fergana State University, 2024)
In this article, it is revealed that the creativity of leading personnel serves for the all-round development of the modern state and society management. In the current period, the need for a mature leader and his spiritual characteristics to be compatible with modernization and integration has been researched. For this, no matter how beautiful or ugly the moral qualities of people are, they are revealed only in the activities of social and political management.